Spatial analysis of labor force dynamics in selected EU countries - Beutl, Sarah; Formánek, Tomáš; Čížek, Ondřej; Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky (2018)
This master thesis is addressing spatial dependence on employment rates of the population and within subgroups of the population. The attention is also directed at the changes over time as well as the differences between subgroups of the population.Theory for spatial analysis, its beginnings and models are explained, and some literature review concerning the labour market, with attention on the market in the European Union, is done. Concentration on the employment part is intensified for the selected countries Austria, Belgium, the Czech Republic, Denmark, France, Germany, Hungary, Italy, the Netherlands, Poland, Slovenia and Slovakia. Subgroups of the population are used for modelling which are gender, age and educational attainment.The practical part starts with a model analysis, supported by the literature review done. The appearance of spatial dependence is investigated for the employment rates of the years 2005, 2010 and 2015 for the total working population as well as for the year 2015 for subgroups of the population. Local spatial analysis is used to plot hotspots for the selected countries, years and groups. Comparison of global and local analyses done is made.Given the results of the thesis, spatial dependence occurs for employment rates of the chosen countries. Statistically significant models found with spatial parameters included are showing better results than models excluding spatiality. Local analysis done for spatiality are showing changing trends for hotspots plots over time and subgroups.
Vedoucí práce: Tomáš Formánek
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta informatiky a statistiky, 2018
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2018
Způsob přístupu: Internet
Keywords: quantitative economic analysis [obor dipl. práce]; diplomové práce; master's theses